Photocatalytic CO2 reduction to HCOOH over core-shell Cu@Cu2O catalysts - Hui Wang (Elsevier, 2022)
Photocatalytic conversion of CO2 into HCOOH is a highly anticipated way to address the long-term demand of energy supply. Herein, we report the fabrication of uniform core-shell nanoparticles composed of a Cu core encapsulated by a Cu2O shell by thermal treatment of a Cu-MOF precursor. Impressively, Cu@Cu2O/C-350 exhibited the catalytic activity in CO2 reduction to HCOOH, attaining a HCOOH production rate of 31 μg/h without any additives at room temperature. Further mechanistic studies indicated that surface Cu2O shell was acted as the active sites for the adsorption and activation of CO2.